Enhanced electrical properties and conduction mechanism of A-site rare-earth Nd-substituted CaBi2Nb2O9. (4th August 2022) - Chen, Juan-Nan; Wang, Qian; Lu, Hong-Ting; Zhao, Xian; Wang, Chun-Ming
Abstract: Calcium bismuth niobate (CaBi2 Nb2 O9, CBN) is considered to be one of the most promising high-temperature (HT) piezoelectric materials owing to its high Curie temperature of ∼940 °C, however, its low electrical resistance and poor piezoelectric properties at elevated temperatures limit its applications at high temperatures. In this work, we report the significantly enhanced dc electrical resistivity and piezoelectric performance of CBN ceramics through rare-earth Nd-substitution. The crystal structure, microstructure, and dielectric, electrical, ferroelectric and piezoelectric properties of Nd-modified CBN with nominal compositions of Ca1− x Nd x Bi2 Nb2 O9 (CBN-100 x Nd) have been investigated in detail. The results indicate that the substitutions of Nd 3+ ions for Ca 2+ ions increase the piezoelectric properties, and reduce the dielectric loss tan δ at high temperatures. The dc and ac conduction mechanisms indicate that the conduction mechanism is closely related to oxygen vacancies that are reduced through the donor substitutions of Nd 3+ for Ca 2+, thereby resulting in a significant improvement in the dc electrical resistivity. The optimal composition of CBN-3Nd exhibits a high piezoelectric constant d 33 of 13.5 pC N −1, and a high Curie temperature T c of 948 °C. More importantly, the CBN-3Nd exhibits good thermal stability of the electrical properties ( ρ = 2.6 × 10 7 Ω cm at 500 °C and 1.8 × 10 6 Ω cm at 600 °C, k p = 6.1%–6.2% at RT ∼ 500 °C), which demonstrates that the Nd-modified CBN ceramics are promising piezoelectric materials for use in HT piezoelectric sensors.